Electrochemical surface modification on CuPdAu/C with extraordinary behavior toward formic acid/formate oxidation. (10th August 2016) - Mao, Han; Huang, Tao; Yu, Aishui
Abstract: In this article we innovatively propose a new surface modification strategy which applies a chronoamperometry on CuPdAu/C to get the surface copper removed CuAuPd/C (SCR-CuAuPd/C). Moreover, the chronoamperometric process can also modify the surface constitution with oxides such as PdO2 and Au2 O3 . The removal of surface Cu will diminish the drawbacks brought by the instability of surface Cu in alkaline media, and the oxides like PdO2 will help oxidize COad and thus reduce catalyst poisoning. The electrochemical measurements confirm the positive effect of chronoamperometric treatment, the SCR-CuPdAu/C achieve objective progress after chronoamperometric treatment, with highest activity and anti-poisoning properties toward formic acid/formate oxidation in both acidic and alkaline media. Graphical abstract: Highlights: Surface Cu removal for CuPdAu/C via chronoamperometric method. Enhanced electrocatalytic activity and stability due to the surface Cu removal. Durable catalysis of HCOOH/HCOO − oxidation for CuPdAu/C in both acidic and alkaline media.